2017
DOI: 10.1155/2017/5343010
|View full text |Cite
|
Sign up to set email alerts
|

Ferulic Acid Suppresses AmyloidβProduction in the Human Lens Epithelial Cell Stimulated with Hydrogen Peroxide

Abstract: It is well known that oxidative stresses induce the production of amyloid β (Aβ) in the brain, lens, and retina, leading to age-related diseases. In the present study, we investigated the effects of ferulic acid on the Aβ levels in H2O2-stimulated human lens epithelial (HLE) SRA 01/04 cells. Three types of Aβ peptides (Aβ1-40, Aβ1-42, and Aβ1-43) were measured by ELISA, and the levels of mRNA for the expressed proteins related to Aβ production (APP, BACE1, and PS proteins) and degradation (ADAM10, NEP, and ECE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…[30][31][32][33][34][35] We have also reported that the stimulation of ROS hydrogen peroxide augmented gene expression of the proteins related to Ab production, resulting in the production of three types of Ab peptides (Ab 1-40 , Ab , and Ab ) in the human lens epithelial SRA01/04 cells. 36 In addition, we used lens epithelium located on the outer surface of the lens in this FIGURE 7. Gene expression of (A) APP, (B) BACE1, (C) PS1, (D) PS2, (E) ADAM10, (F) NEP, and (G) ECE1 in the lens epithelium of cataract patients with or without cortical opacification.…”
Section: Discussionmentioning
confidence: 99%
“…[30][31][32][33][34][35] We have also reported that the stimulation of ROS hydrogen peroxide augmented gene expression of the proteins related to Ab production, resulting in the production of three types of Ab peptides (Ab 1-40 , Ab , and Ab ) in the human lens epithelial SRA01/04 cells. 36 In addition, we used lens epithelium located on the outer surface of the lens in this FIGURE 7. Gene expression of (A) APP, (B) BACE1, (C) PS1, (D) PS2, (E) ADAM10, (F) NEP, and (G) ECE1 in the lens epithelium of cataract patients with or without cortical opacification.…”
Section: Discussionmentioning
confidence: 99%
“…The human lens epithelial cell line SRA 01/04 (HLE cell) was cultured under humidified air containing 5% CO 2 at 37 • C, following our previous reports [31,35]. Briefly, HLE cells were cultured in Dulbecco's modified Eagle's medium with gentamicin (10 mg/L) and 10% (v/v) heat-inactivated fetal bovine serum.…”
Section: Measurement Of Toxicity Using Cultured Human Lens Cellsmentioning
confidence: 99%
“…The mechanism of action of Cur on AD has been reported to involve the inhibition of Aβ aggregation, an increase in BDNF, and a decrease in tau phosphorylation [ 10 , 30 , 31 ]. On the other hand, research has shown that FA inhibits Aβ production via downregulation of APP and β-secretase [ 32 ], has potent antioxidant properties, and protects neurons from Aβ-induced neurotoxicity mainly although we previously confirmed FA also has anti-amyloidogenic effect for Aβ [ 21 ]. We hypothesized that FA and Cur might complement each other based on such reports.…”
Section: Discussionmentioning
confidence: 92%